“Malo” dan Penegakan Karakter Kejujuran: Tafsir Budaya(wan) Madura atas “Sisi Gelap” Pengelolaan Keuangan Daerah - Setiawan, Achdiar Redy (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 2 (2019)DO - 10.24843/JIAB.2019.v14.i02.p10, 2019)
The study aims to explore the (Madura) cultural interpretations over multiple interpretations of "Tactical Fund” in the local government financial managements namely “system-driven (un) fraud.” By using bid’ah hermeneutics methodology, an extended form of the hermeneutic. Multiple interpretations of government apparatus criticized by interpretations of cultural values ??as an essential life guidance reference for Maduranese. Cultural values ??in this study were derived from a Madura cultural observer and relevant literature. The findings of this research concluded that honesty is a critical value that should be embodied by all Maduranese, government apparatus entailed. Reinterpretation of the “malo” concept is one of the important advices being proposed as solution based on the cultural perspective. Keywords: Regional fnancial manaement, bid’ah hermeneutics, “malo” value, honesty culture